THE ROLE OF SHARIA FINANCIAL SERVICES IN REDUCING THE RATE OF MIGRANT LABOR - Setiawan, Edy; Busthomi, Achmad Otong (IAIN Syekh Nurjati Cirebon, 2023)
Abstract This article confirms that Islamic financial services initiate and carry out local economic empowerment in the regions. The study will be carried out in areas that have so far been considered to be major suppliers of Indonesian Migrant Workers (TKI) abroad. One of them is looking at the role of Islamic financial services in the form of the treasury of Money and Finance (BMT) and Sharia cooperatives, which are currently emerging in the community. The role of Islamic financial services in several regions was able to restrain the flow of migration abroad. The method developed is to provide various forms of financial services as business capital.Keywords: Migrant Workers; Sharia Financial Institutions; Sharia Financial Services.